Phase II trial of patupilone in patients with brain metastases from breast cancer. (26th January 2014) - Peereboom, David M.; Murphy, Conleth; Ahluwalia, Manmeet S.; Conlin, Alison; Eichler, April; Van Poznak, Catherine; Baar, Joseph; Elson, Paul; Seidman, Andrew D.
Abstract: Background: For patients with progressive breast cancer brain metastasis (BCBM) after whole brain radiotherapy (WBRT), few options exist. Patupilone is an epothilone that crosses the blood–brain barrier. We hypothesized that patupilone would produce a 35% 3-month CNS progression-free survival in women with BCBM after WBRT. Methods: This multicenter phase II trial included 2 cohorts. Group A included women with progressive BCBM after WBRT. Group B was an exploratory cohort of patients with either leptomeningeal metastases or untreated brain metastases. The primary goal was to observe a 35% 3-month CNS progression-free survival in Group A. The sample size was 45 for Group A and 10 for Group B. Patients received patupilone 10 mg/m 2 once every 3 weeks until progression. Responses were scored according to the Macdonald criteria. Results: Fifty-five patients (45 in Group A, 10 in Group B) enrolled. In Group A, the 3-month CNS progression-free survival was 27%, the median overall survival was 12.7 months, and the overall response rate was 9%. In Group B, which enrolled 5 patients with leptomeningeal disease and 5 with no prior WBRT, no responses occurred and 8 patients had CNS progression before 3 months. Systemic responses occurred in 15% of patients, including a complete response in liver metastases. Diarrhea occurred in 87% of patients; 25% had grade 3 and 4 adverse events. Conclusions: Patupilone in patients with BCBM did not meet the efficacy criteria and had significant gastrointestinal toxicity. Further study of brain-penetrant agents is warranted for patients with CNS metastases from breast cancer.